152 Predictive Factors for Survival after Paediatric Out-Of-Hospital Cardiac Arrest: A UK Multicentre Cohort Study. (October 2012) - Scholefield, B; Raman, S; Hussey, A; Haigh, F; Kanthimathinathan, HK; Skellett, S; Peters, M; Duncan, H; Morris, K
Abstract : Introduction: Survival after paediatric out-of-hospital cardiac arrest (OHCA) is poor, even amongst those who are successfully resuscitated and admitted to PICU. Better prediction of survival would be of benefit to clinical teams and to research teams designing trials. This study aimed to identify predictive factors for survival to inform the design of a post-OHCA intervention trial. Method: Retrospective, cohort study of 155 infants and children (1 day to 16 years) admitted to 3 UK PICUs after OHCA (2004–2010). Variables relating to a) the resuscitation period (Utstein) and b) the post-resuscitation period were included in two multivariate stepwise regression models to identify predictive factors for survival to PICU discharge. Results: 32% (50/155) children survived to PICU discharge. Resuscitation variables individually associated with improved survival included; presenting in a shockable rhythm, shorter duration of arrest, return of spontaneous cardiac output prior to arrival in the emergency department and lower number of epinephrine doses. Post-resuscitation variables individually associated with improved survival included; higher arterial pH, lower blood lactate, lower maximum glucose, higher base excess and responsive pupils. Results of multivariate stepwise regression models are reported in table. Conclusion: This large UK study is the first to identify lactate as one of the key predictors of paediatric OHCA survival in patients admitted to PICU. Development of an accurate prediction tool would assist trial design and prognostication after paediatric OHCA.